Analisa Keandalan Jaringan Local Area Network (LAN) PT. Chevron Pacific Indonesia- Duri Menggunakan Distribusi Weibull - Ali, Irsan Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Reliability is the ability of a system or component performs all the functions needed specific time period. Reliability Networking Local Area Network (LAN) is determined from the failure rate. This journal discusses Reliability Networking LAN analysis based on the value of the MTTF. This failure occurs on a physical disorder that includes transmission side include electric, ups, switches, transmission (fiber optic), converters, patch cords, connectors and others. The method that used in analyzing reliability is Distribusi Weibull. The calculation method of the Weibull distribution parameters using LSM. From the calculation, the shape parameter value is 1.9664 and scale parameter value is 3.4039. MTTF value of 0.9936 months, the uptime value of 11.0664 month, reliability value of 0.9222.Keywords : LAN, reliability, distribusi weibull.